Web-Based Source To Source Converter - Chooi, Kar Jian (2021)
Software maintenance activity in the software development life cycle is becoming more difficult over time. Hence, many companies are interested in using automated code translation techniques to maintain their software. However, the existing automated code translators are still error prone and inefficient. Thus, this project is developed to improve accuracy of code conversion between high level languages, eliminate the need of manual conversion and promote universally compatible code conversion. The core functionality of the project will be developed based on a transpiler which convert codes into an abstract intermediate representation and to the desired target language. In this project, a code transpilation framework are developed with a frontend website. The code conversion model could achieve 90% accuracy. The result of the usability testing also showed that the system achieved a positive usability result. In conclusion, the project has been implemented successfully as it met the project’s objectives.